THE ESSENTIALITY OF THE NUSANTARA TRADITIONAL CALENDAR - Hikmatul Adhiyah Syam (Fakultas Syari'ah dan Hukum UIN Walisongo, 2021)
Today, tomorrow, yesterday, and later is the time because this life will always talk about the time that can affect the pattern of life in an environment. So that the existence of time becomes important. Based on this, a time system was compiled using the circulation of celestial bodies. Previous people have inherited the traditional calendar in their respective regions. This adapts to the condition of the community and its environment. The research question in this research is how the interpretations of the traditional calendars in the archipelago. The purpose of this research is to explore the essential meaning of the traditional calendars in the archipelago. The method used in this research is library research. This method is used to describe the various existing sources. The results showed that the calendar in each region has its own meaning for the wearer. The Batak calendar is used to determine good and bad days, the Pranatamangsa calendar for season markers, the Saka calendar for marking religious rituals, the Islamic Javanese calendar for historical momentum markers and Islamic teachings, the Bugis calendar for guidelines for daily activities and the Maluku calendar for marking the time of manufacture boat.